2011
DOI: 10.1088/1751-8113/44/28/285204
|View full text |Cite
|
Sign up to set email alerts
|

A unifying perspective on the Moyal and Voros products and their physical meanings

Abstract: The Moyal and Voros formulations of non-commutative quantum field theory has been a point of controversy in the recent past. Here we address this issue in the context of non-commutative nonrelativistic quantum mechanics. In particular we show that the two formulations simply correspond to two different representations associated with two different choices of basis on the quantum Hilbert space. From a mathematical perspective the two formulations are therefore completely equivalent, but we also argue that only … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 31 publications
1
63
0
1
Order By: Relevance
“…In this connection, it may be recalled that the essential idea of this development is to define the fields as mean value over coherent states of the noncommutative plane, such that a star product needs not be introduced. We further note that recently it has been shown that the coherent state approach can be summarized through the introduction of a new multiplication rule which is known as Voros star-product [10,11], [12,13,14]. Nevertheless, and most importantly, physics turns out be independent from the choice of the type of product [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, it may be recalled that the essential idea of this development is to define the fields as mean value over coherent states of the noncommutative plane, such that a star product needs not be introduced. We further note that recently it has been shown that the coherent state approach can be summarized through the introduction of a new multiplication rule which is known as Voros star-product [10,11], [12,13,14]. Nevertheless, and most importantly, physics turns out be independent from the choice of the type of product [15].…”
Section: Introductionmentioning
confidence: 99%
“…Also, from (24) it is easy see that the introduction of a minimal length preserves the asymptotically free behavior at short distance characterizing the non-Abelian character of the strong interactions.…”
Section: Final Remarksmentioning
confidence: 99%
“…Interestingly, it is observed that the term proportional to θ is ultraviolet finite. Another important point to be mentioned in our discussion comes from the explicit appearance of the cutoff Λ in (24). Evidently, at distances higher than 1 / Λ the interaction potential (24) is convergent.…”
Section: Yang-mills In the Presence Of A Minimal Lengthmentioning
confidence: 99%
“…To do this, the source δ (3) (x − y) is replaced by the smeared source e θ 2 ∇ 2 δ (3) (x − y). Hence expression (18) reduces to…”
Section: Finite Electrodynamicsmentioning
confidence: 99%
“…The key ingredient of this development is to define the fields as mean value over coherent states of the noncommutative plane, such that a star product needs not be introduced. More recently, it has been shown that the coherent state approach can be summarized through the introduction of a new multiplication rule which is known as Voros star-product [14,15], [16,17,18]. Anyway, physics turns out be independent from the choice of the type of product [19].…”
Section: Introductionmentioning
confidence: 98%